Analysis of Aggregate Planning with a Chase Strategy Approach to Reduce Production Costs - Dwitami, Fadila Antovi; Sukanta (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
In Indonesia, there are already many established companies. Starting from a more focused industry/manufacturing, services, and trade. Many companies are starting to look for ways to increase the company's profits. The manufacturing industry sector itself certainly spends a lot on production. Therefore, the company is looking for a method that can minimize production costs. The purpose of this study is to minimize production costs. The method used is the aggregate chase strategy method. The results showed that planning using the aggregate chase strategy method can minimize production costs. After comparing the company's total production cost in 2020 amounted to Rp. 8,952,896,124 with the results of planning using the aggregate method of chase strategy in 2021 amounting to Rp. 8,428,458,444, obtained a gap of Rp. 524,437,680. By planning production costs using the aggregate method, the company can reduce the amount of labor and utilize the amount of labor available as much as possible without incurring workers' overtime costs. Then the company can save on production costs.